Marketing of high technology and wealth creation: a feedback from Muslim high technology practitioners in Malaysia - Mhd. Sarif, Suhaimi (2010)
This study attempts to explore the views of Muslim high technology practitioners in Malaysia pertaining to marketing of high technology in creating wealth through the high technology-based sector. The high technology sector requires innovation, which is essentially related to knowledge production activities. While knowledge is very fundamental in Islam, Muslims could practice of marketing of high technology activities that integrated into high technology ventures. This study used e-mail survey with 74 Muslim high technology practitioners in three high technology locations: Cyberjaya, Technology Park Malaysia (TPM), and Selangor Science Park (SSP). The preliminary results suggest marketing of high technology is feasible to create wealth in the high technology sector because this sector encourages entrepreneurship and innovativeness, which is highly recommended in Islam. However, the participation of Muslim community in this sector is still inadequate despite the incentives provided by the government through its Multimedia Malaysia project.